Existence of solution for a supercritical nonlinear Schrödinger equation. Issue 1 (2nd January 2023) - Faria, Luiz F. O.; Montenegro, Marcelo
Abstract : We show existence of solution for a supercritical nonlinear Schrödinger equation on the whole R N by means of an approximation scheme. We prove a Sobolev embedding corresponding to the variable exponent of the equation.